2018
DOI: 10.1021/acsenergylett.8b01201
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Current and Voltage Losses to Reach 25% Efficient Monolithic Two-Terminal Perovskite–Silicon Tandem Solar Cells

Abstract: The rapid rise in efficiency and tunable bandgap of metal-halide perovskites makes them highly attractive for use in tandems on silicon. Recently we demonstrated a perovskite–silicon monolithic two-terminal tandem with 23.6% power conversion efficiency. Here, we present work on optical optimization to improve light harvesting that includes thinning out the top transparent electrode to reduce front-surface reflection and parasitic absorption; introducing metal fingers to minimize series resistance losses; and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
203
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 213 publications
(209 citation statements)
references
References 75 publications
4
203
0
2
Order By: Relevance
“…Apart from being a diffusion barrier, the ZTO layer was also necessary for achieving a low contact resistance with an ITO and a high fill factor. As a result, the two‐terminal tandem with 1 cm 2 active area reached a PCE of 23.6%, with negligible parasitic absorption and excellent stability for 1000 h. In 2018, the same group improved the two‐terminal tandem efficiency to 25.0%, by minimizing the reflection, managing the absorber bandgap and optimizing the device contact. To reduce the reflection, the front ITO electrode was thinned to 50–60 nm, which blue‐shifted the reflection maximum to 400 nm and simultaneously decreased the parasitic absorption.…”
Section: Current Research Trends In Tandem Devicesmentioning
confidence: 98%
See 4 more Smart Citations
“…Apart from being a diffusion barrier, the ZTO layer was also necessary for achieving a low contact resistance with an ITO and a high fill factor. As a result, the two‐terminal tandem with 1 cm 2 active area reached a PCE of 23.6%, with negligible parasitic absorption and excellent stability for 1000 h. In 2018, the same group improved the two‐terminal tandem efficiency to 25.0%, by minimizing the reflection, managing the absorber bandgap and optimizing the device contact. To reduce the reflection, the front ITO electrode was thinned to 50–60 nm, which blue‐shifted the reflection maximum to 400 nm and simultaneously decreased the parasitic absorption.…”
Section: Current Research Trends In Tandem Devicesmentioning
confidence: 98%
“…There are several well‐identified routes to minimize a parasitic loss, and one strategy is reducing the layer thickness of transparent electrodes . By adjusting the thickness of front ITO layers from 150 to 60 nm, both the parasitic absorption and reflection were efficiently decreased. However, the optical simulation indicated that thicker ITO layers give rise to significant parasitic absorption, whereas thinner layers result in a reduced fill factor (FF) due to high series resistance .…”
Section: Perovskite Tandem Progressmentioning
confidence: 99%
See 3 more Smart Citations